Pembuktian Paternitas Berbasis DNA dan Hak Waris Anak Luar Nikah: Studi Komparatif Indonesia dan Turki dalam Perspektif Maqasid Shariah Thahir Ibn ‘Asyur - Safrida Ramadhania; Abd Rouf (Lembaga Yasin AlSys, 2026)
The development of DNA testing technology has increased the ability to prove the biological relationship between a child and their biological father; however, this scientific certainty has not been fully followed by legal certainty in the field of inheritance. This study aims to analyze the relationship between DNA-based proof of paternity and the inheritance rights of children born out of wedlock in Indonesian Islamic law, compare it with the Turkish legal system, and formulate a model for protecting economic rights in accordance with the perspective of maqāṣid al-sharī‘ah of Thahir Ibn ‘Āsyūr. This study used a normative legal research method with statutory, conceptual, comparative, and maqāṣid al-sharī‘ah approaches. Primary legal materials in the form of laws and regulations, court decisions, fatwas, and Turkish legal provisions were analyzed descriptively-analytically and prescriptively. The results show that Constitutional Court Decision Number 46/PUU-VIII/2010 has opened civil relations between children born out of wedlock and their biological fathers that can be proven through science and technology, including DNA testing. However, the Compilation of Islamic Law and MUI Fatwa Number 11 of 2012 continue to limit lineage relations and inheritance rights to the mother and her family. Conversely, Turkish law shows a clearer connection between proof of paternity, determination of the child’s legal status, and inheritance rights. The conclusion of this study affirms that the protection of the economic rights of children born out of wedlock in Indonesian Islamic law can be reconstructed through an obligatory bequest that is imperative after the biological relationship has been proven through DNA and determined by a court. These findings contribute to the development of Islamic family law and inheritance law by offering a child protection model oriented toward public benefit without disregarding the principle of lineage.